Sustainable Health in the Era of Work from Anywhere - Pradeep Kumar Bolisetty; Pooja Sharma; Sanjay Bhattacharya (Australasian Accounting, Business and Finance Journal, 2023)
Purpose: COVID- 19 paved the way for a hybrid work model; wherein employees can work from the office or work from home, or work from anywhere. The model of working from anywhere offers flexibility and autonomy to employees to a great extent. However, its ramifications and consequences pertaining to the health of the employees are yet to be fully explored. This study tries to understand the impact of work from anywhere on employees' health. Design/ Methodology/ Approach: Data was collected from 112 people who have worked in both work from office and work from home models. The analytic Hierarchy Process was used for data analysis. Findings: AHP analysis of mental health data considering stress, anxiety, and worry shows that mental health is better during work from anywhere than working from the office. Analysis of emotional health using AHP shows that emotional health is better during work from anywhere than during work from the office, based on employee relationships. It is evident from spiritual health data that spiritual health did improve during work from anywhere as compared to working from office. It is also clear that financial health is better during work from anywhere when compared with working from the office, which depends on employees' savings and expenditures. Originality/ Value: The research contributes significantly to organizations that are adopting a hybrid work model.
Keywords: Sustainable health; SDG goal; Hybrid work model; Work from anywhere